Advances in Dam Engineering - Hariri-Ardebili, M. Amin; Salamon, Jerzy; Mazzà, Guido; Tosun, Hasan; Xu, Bin (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Expansion of water resources is a key factor in the socio-economic development of all countries. Dams play a critical role in water storage, especially for areas with unequal rainfall and limited water availability. While the safety of existing dams, periodic re-evaluations and life extensions are the primary objectives in developed countries, the design and construction of new dams are the main concerns in developing countries. The role of dam engineers has greatly changed over recent decades. Thanks to new technologies, the surveillance, monitoring, design and analysis tasks involved in this process have significantly improved. The current edited book is a collection of dam-related papers. The overall aim of this edited book is to improve modeling, simulation and field measurements for different dam types (i.e. concrete gravity dams, concrete arch dams, and embankments). The articles cover a wide range of topics on the subject of dams, and reflect the scientific efforts and engineering approaches in this challenging and exciting research field.